Jenis Tumbuhan yang Digunakan sebagai Obat Tradisional Di Daerah Eks-Karesidenan Surakarta - Dewantari, Rinika; L, Monika Lintang; Nurmiyati, Nurmiyati (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
Ethnobotany is study about relationship between humans and plants. Ethnobotany explain how plants are used by humans for their needs. The development of science and technology about ethnobotany is developing. Nowadays, ethnobotany is study of study of human relationships with natural resources and the environment. Ethnopharmacology is pharmaceutical science that study about how to make medicines from natural ingredients. Traditional medicine has been used from generation to generations. Economic crisis in indonesia causes the price of the medicine is expensive. The high cost of chemical medicine due to chemicals need to be imported from abroad. Such conditions encourage Indonesian people to utilize plants as a traditional medicine. To support the environment remains sustainable and keep the medicinal plants remain, it is necessary to develop the activities of medicinal plants cultivation.